Unraveling the complexity of the impact of physical exercise on male reproductive functions: a review of both sides of a coin - Adelowo, Olayinka Emmanuel; Akindele, Blessing Monica; Adegbola, Cecilia Adedeji; Oyedokun, Precious Adeoye; Akhigbe, Tunmise Maryanne; Akhigbe, Roland Eghoghosoa (Frontiers in Physiology, 2024)
Regular exercise is widely recognized for its numerous physical and mental benefits, but its effects on male reproductive health are less understood. This review aims to summarize the current evidence on the impact of exercise on male reproduction, including reproductive hormone regulation, spermatogenesis sperm quality, and fertility. Moderate exercise improves sperm quality, increasing count, motility, and morphology, while excessive and severe exercise may have detrimental effects. Exercise positively influences fertility by reducing oxidative stress and enhancing sperm DNA integrity. Regular physical activity regulates reproductive hormones, including testosterone, follicle-stimulating hormone, and luteinizing hormone. Exercise-induced weight management and improved insulin sensitivity also contribute to better reproductive health. In conclusion, exercise has a profound impact on male reproductive health, with moderate physical activity promoting improved hormonal balance, sperm quality, and fertility. However, severe/excessive exercise exerts negative effects. These findings imply that a balanced exercise routine, usually mild to moderate, combined with a healthy lifestyle is essential for optimal male reproductive health. However, once exercise is severe and prolonged, it could impair male reproductive health. Further research is needed to understand the mechanisms underlying the exercise-reproduction relationship fully.